THE EFFECT OF CONSTAC PLUS IN THE MANAGEMENT OF SEVERE CHRONIC CONSTIPATION: A PILOT STUDY - Ashwin, *Porwal; Paresh, Gandhi; Jaya, Maheshwari; Kulkarni, Deepak (International Journal of Ayurveda and Pharma Research, 2016)
The purpose of this study was to evaluate the efficacy of CONSTAC PLUS granulation in the management of severe chronic constipation. Total 450 patients were enrolled to receive a CONSTAC PLUS for maximum 60 days. Out of 450 patients, 33 were lost to follow up. The symptoms of constipation were evaluated by Longos Obstructed Defecation Syndrome (ODS) score system. Patients quality of life was assessed by the Patient Assessment of Constipation-Quality of Life Questionnaire and stool consistency were assessed by â€œBristol stool form scaleâ€ before and after 15, 30 and 60 days. Analysis done for 417 patients. After treatment there was significant (p<0.005) improvement in defecation frequency per week. There was significant reduction in rectoperinieal pain and discomfort, straining intensity, average time spent on toilet for bowel evacuation and digitations score. Stool consistency were significantly (p<0.005) improved in all follow-up visits. Quality of life also significantly improved in all follow up visits. During study abdominal pain/cramping (n= 13/ 3.12%), bloating (n= 11/ 2.64%), diarrhea (n= 9/ 2.16%), and passing gas (n= 17/ 4.098%) adverse events were more commonly reported. All were treated by medical management. This result proves CONSTAC PLUS is an effective and safe herbal laxative formulation for severe chronic constipation.